Management in the Digital Age Will China Surpass Silicon Valley? - Steiber, Annika (SpringerBriefs in Business,, 2018)
In this Springer Brief, the author introduces how Chinese firms are successfully using their own variants of the 'Silicon Valley Approach' to management. The author begins the discussion by deliberating on the extent to which management models need to be re-invented. A fundamentally new approach is then introduced, which already exists and is proving itself in practice at some of Silicon Valley ́s most dynamic firms. The author finds that the Chinese management models, in comparison, may be even more advanced. If true, this could have profound implications for managers everywhere. The author acknowledges that no management model fails (or succeeds) every time. Skeptics can point to big bureaucratic firms that continue to prosper, as well as to radical innovators that have gone under. This book brings to light the need that has emerged for a model that will give companies their best chances of thriving amid the VUCA whirlwind. A comb ination of evidence and informed opinion indicates the old management model has run its course. .